Mad to be normal [videorecording (DVD)] - Mullan, Bob; Mullan, Bob; Moss, Elisabeth, 1982-; Tennant, David, 1971-; Byrne, Gabriel, 1950- (Samuel Goldwyn Films, 2018)
Scottish psychiatrist R.D. Laing creates controversy within his profession for his approaches to the field and a community he creates for his patients.